Perbaikan Proses Bisnis Logistik Sampah di Kota Cirebon Menggunakan Metode Business Process Improvement (BPI) - Sutandi Sutandi (Jurnal Logistik Indonesia, 2020)
One of the main issues in the city of Cirebon is the problem of waste management. The City of Cirebon's Environmental Service is tasked with managing waste from Households and Industries to the Garbage Collection Site (TPS) to the Final Disposal Site (TPA). The business process of transporting waste from TPS to TPA still often experiences obstacles, one of which is the delay in transportation from TPS to TPA because it does not pay attention to the connectivity of waste flow and information flow as a single entity that forms a waste logistics network. The purpose of this study is to propose the design of waste logistics policy through improving the waste logistics business process. The research method applied by using the fishbone diagram and five whys analysis methods sourced from interviews, and field observations in finding the fundamental problems of each business process. The basic problem based on the results of the analysis is the accumulation of waste at the TPS. With the results of observations it will be designed improvements with streamlining tools analysis tools on Business Process Improvement (BPI) in presenting business process recommendations. Based on business process recommendations, then run a simulation to see performance improvements for each business process, with an increase in the performance of garbage delivery trucks from TPS to TPA by 34.31% so as to reduce the accumulation of waste in TPS.